Beneficial Impact of Excess Mg on Flux Pinning in Bulk MgB2 Synthesized with Ag Addition and Carbon Encapsulated Boron. Issue 8 (21st June 2019) - Arvapalli, Sai S.; Miryala, Muralidhar; Murakami, Masato
Abstract : Silver addition has been known to improve mechanical and superconducting performance of bulk magnesium boride (MgB2 ) superconductor synthesized via solid state sintering. While formation of pinning phases and impurities such as Ag–Mg phases and MgO, respectively, responsible for high performance, part of the Mg in initial mixture will be expected to be consumed by silver. In this work, the authors add varied amounts of Mg systematically such as x : 2 (while x = 1.05, 1.075, 1.1, 1.125, 1.15) ratio of Mg:B instead of usual stoichiometric ratio of 1:2. To obtain high superconducting properties, the authors use carbon encapsulated boron (1.5% carbon) along with 4 wt% Ag. X‐ray diffraction analysis shows the presence of Ag–Mg phases and minute amount of MgO. Superconducting quantum interference device (SQUID) measurements indicate that high irreversibility field (4.76 T) and large J c of 520, 440, and 347 kA cm −2 at 10, 15, and 20 K, respectively, at self‐field was exhibited in sample with x = 1.075. Flux pinning force studies are done to analyze the effect of secondary phases formed. All results analyzed explain the improved critical current performance based on nanometer‐sized Ag–Mg particles in the final product. Abstract : In MgB2 Bulk superconductors, the authors add silver‐ and carbon‐coated boron to improve pinning via nano Ag–Mg phases' formation and uniform carbon substitution. The authors report that to balance the Mg losses from these additional phases, 7.5‐wt% excess is suitable for producing best performance MgB2 bulk. The authors observe superior critical current densities, which is crucial for superconducting super magnet applications.